Cartel formation with endogenous capacity and demand uncertainty - Johannes Paha (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
This article analyzes the strategic decisions of firms whether to establish and adhere to a cartel when they can also shape competition by investing into production capacity while being subject to unexpected demand shocks with persistence. The model shows that a negative demand shock can facilitate cartel formation despite lowering collusive profits. This is because lower demand reduces capacity utilization and makes competition more intense especially when capacities are durable and when demand falls much within a short time. The model also shows that firms with a low discount rate strive for a dominant position in the market which results in asymmetric capacity distributions. These obstruct collusive strategies. This is interesting because a low discount rate is usually considered a facilitating factor for collusion.
Keywords: D21; D43; L11; L13; L41; 330; Asymmetric firms; capacity investments; cartel formation; demand shocks; excess capacity